Health systems changes after decentralisation: progress, challenges and dynamics in Pakistan - Shehla Abbas Zaidi; Maryam Bigdeli; Etienne V Langlois; Atif Riaz; David W Orr; Nasir Idrees; Jesse B Bump (BMJ Global Health)
Decentralisation is widely practised but its scrutiny tends to focus on structural and authority changes or outcomes. Politics and process of devolution implementation needs to be better understood to evaluate how national governments use the enhanced decision space for bringing improvements in the health system and the underlying challenges faced. We use the example of Pakistan’s radical, politically driven provincial devolution to analyse how national structures use decentralisation opportunities for improved health planning, spending and carrying out transformations to the health system. Our narrative draws on secondary data sources from the PRIMASYS study, supplemented with policy roundtable notes from Pakistan.Our analysis shows that in decentralised Pakistan, health became prioritised for increased government resources and achieved good budgetary use, major strides were made contextualised sector-wide health planning and legislations, and a proliferation seen in governance measures to improve and regulate healthcare delivery. Despite a disadvantaged and abrupt start to devolution, high ownership by politicians and bureaucracy in provincial governments led to resourcing, planning and innovations. However, effective translation remained impeded by weak institutional capacity, feeble federal–provincial coordination and vulnerability to interference by local elites.Building on this illustrative example, we propose (1) political management of decentralisation for effective national coordination, sustaining stable leadership and protecting from political interfere by local elites; (2) investment in stewardship capacity in the devolved structures as well as the central ministry to deliver on new roles.